THE ROLE OF LANGUAGE STYLE AND COMMUNICATION IN BOOSTING SALES THROUGH LIVE STREAMING ON TIKTOK - Tarigan, Karisma E.; Sembiring, Agita Br (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Language style is a way of speaking/writing that depends on the situation of the person (or people) you are speaking or writing to. Language style refers to the selection of linguistic forms to convey social or artistic effects. In communication, people usually use formal or informal language, depending on the situation they are communicating with others. Language style also tells the listener to accept what is being said, whether it is serious, ironic, funny, or otherwise (Saputri et al., 2022). According to (Joos Theory Author et al., 2023) in (Joos in Chaer and Agustina (1995: 92)) divides variety of language into five styles, they are; frozen style, formal style, consultative style, casual style, and intimate style. This study investigates how the role of language style in TikTok live streaming in selling products on the platform with qualitative methods. Qualitative is used to describe and analyse the phenomena that usually occur in daily activities and does not deal with numbers as a data (Saputri et al., 2022). In collecting data, videos were taken from three tiktok accounts, namely the Elformula Official, Nalalacollection, and FJ.bottle accounts with a duration of 10 minutes each. language style plays a critical role in the success of live-streaming sales on TikTok by fostering effective communication and engaging interaction between sellers and consumers. The casual and intimate language styles dominate this environment, creating a friendly and relatable atmosphere that appeals to TikTok's diverse audience. Sellers use dynamic, easy-to-understand, and personalized language to build trust and establish a connection with their viewers, enhancing customer engagement and loyalty. Keywords: Language style; Semantics; Social Media; Tiktok.